Bioanalytical method validation and application to a phase 1, double-blind, randomized pharmacokinetic trial of a standardized Centella asiatica (L.) Urban water extract product in healthy older adults - Kirsten M. Wright; Kirsten M. Wright; Melissa Bollen; Melissa Bollen; Jason David; Bridgette Mepham; Armando Alcázar Magaña; Armando Alcázar Magaña; Christine McClure; Claudia S. Maier; Claudia S. Maier; Joseph F. Quinn; et al. (Frontiers Media S.A., 2023)
Introduction:Centella asiatica is an herbaceous plant reputed in Eastern medicine to improve memory. Preclinical studies have shown that C. asiatica aqueous extract (CAW) improves neuronal health, reduces oxidative stress, and positively impacts learning and cognition. This study aimed to develop and validate bioanalytical methods for detecting known bioactive compounds from C. asiatica in human biological matrices and apply them to a human pharmacokinetic trial in healthy older adults.Methods: High performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) was used for detecting triterpenes and caffeoylquinic acids from C. asiatica, or their metabolites, in human plasma and urine. Validation parameters including linearity, precision, accuracy, recovery and thermal stability were evaluated. The method was applied to a Phase I, randomized, double-blind, crossover trial of two doses (2 or 4 g) of a standardized C. asiatica water extract product (CAP) in eight healthy older adults. Pharmacokinetic parameters were measured over a 12-h post administration period and acute safety was assessed.Results: The method satisfied US Food & Drug Administration criteria for linearity and recovery of the analytes of interest in human plasma and urine. The method also satisfied criteria for precision and accuracy at medium and high concentrations. Single administration of 2 and 4 g of CAP was well tolerated and safe in healthy older adults. The parent triterpene glycosides, asiaticoside and madecassoside, were not detected in plasma and in minimal amounts in urinary excretion analyses, while the aglycones, asiatic acid and madecassic acid, showed readily detectable pharmacokinetic profiles. Similarly, the di-caffeoylquinic acids and mono-caffeoylquinic acids were detected in low quantities, while their putative metabolites showed readily detectable pharmacokinetic profiles and urinary excretion.Discussion: This method was able to identify and calculate the concentration of triterpenes and caffeoylquinic acids from C. asiatica, or their metabolites, in human plasma and urine. The oral absorption of these key compounds from CAP, and its acute safety in healthy older adults, support the use of this C. asiatica product in future clinical trials.